THE ROLE OF AN INTERNATIONAL AGRICULTURAL PROGRAMS OFFICE IN A LAND GRANT UNIVERSITY - David M. Henneberry (Revista Mexicana de Agronegocios, 2007)
This article provides an overview of the role that an international agricultural programs officeplays in a land grant university. The discussion is organized along the traditional functionallines of teaching, research and extension. The importance of internationalization of educationis emphasized in order to meet the needs of a rapidly changing global environment. In theconclusions section, seven tips are offered that might help Latin American Universities tointeract more effectively with their counterparts in the United States